The practices of English in Indonesian secondary education: A sequential explanatory study - Siti Sangadatul Latifah; Moh. Arif Mahbub; Ismaili Ismaili (Universitas Islam Malang, 2022)
A growing body of literature on need analysis research has been carried out in indifference areas in various countries around the world. However, need analysis study in Indonesian vocational settings situated in marketing programs is still in its infancy. This article aimed at exploring participants' angles toward the participants' ESP Target Needs in the marketing program at a private Vocational High School (VHS) in East Java, Indonesia. By adapting Hutchinson & Waters' (1987) frameworks, this sequential explanatory mixed-methods (Creswell, 2014, 2018) employed a web-based questionnaire and a series of semi-structured interviews as the instruments. A web-based questionnaire consisting of 9 items: 2 items asking about wants, 2 items asking about necessities, and 5 items asking about lacks was administered to 15 participants who consented to take part in the recent study. Additionally, there were 3 areas of a series of semi-structured interviews exploring participants' and the English teachers' feelings about their wants, necessities, and lacks. A descriptive statistical method using SPSS v.25 was used to analyze the quantitative data, whereas thematic analysis proposed by Widodo (2014) was employed to analyze the qualitative data. The findings indicated that there were various perceptions related to their English target needs. Conclusions, limitations, and recommendations were then discussed.